Effectiveness of WhatsApp-Based Digital Health Education on Self-Care in Diabetes Mellitus Patients: A Quasi-Experimental Study - Wahyuningsih, Atik Setiawan; Ulya, Siti Imroah Layinata (Chakra Brahmanda Lentera Institute, 2026)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder requiring ongoing self-care behavior to prevent complications and improve quality of life. Patient compliance with self-care behavior is still suboptimal. A few facts about the effectiveness of digital health education on self-care behavior and the factors that influence it in primary health care. This study aims to determine the effectiveness of digital health education on Diabetes Mellitus self-care behavior and analyze the dominant factors in improving self-care behavior. Methods: Stage 1 with pre-experimental quantitative pretest-posttest on 106 respondents with informed consent and a simple random sampling technique from 150 Diabetes Mellitus patients. Structured digital health education for one month via WhatsApp. Self-care behavior with 13 items of the Summary of Diabetes Self-care behavior Activities (SDSCA) questionnaire was analyzed using a t-test. Stage 2, with associative quantitative methods, analyzing the effect of disease duration, gender, educational status, and previous educational exposure on self-care behavior; data were analyzed using multiple linear regression, starting with multicollinearity and heteroscedasticity tests. Results: Among the 106 participants, most had lived with diabetes mellitus for ≥5 years (88.7%), were female (71.7%), had completed primary to senior high school education (92.5%), and had never received previous diabetes health education (74.5%). The mean self-care behavior score increased significantly from 39.02 ± 7.96 before the intervention to 46.66 ± 7.60 after the intervention (mean difference = 7.64; t = 11.36; p < 0.001). Multiple linear regression demonstrated that the overall model was significant (F = 5.240, p = 0.001), explaining 17.2% of the variance in self-care behavior improvement. Previous diabetes health education (β = 0.412, p < 0.001) and educational status (β = −0.313, p = 0.002) were significant predictors, whereas duration of illness and gender were not significantly associated with the outcome. Conclusion: WhatsApp-based digital health education effectively improved self-care behavior among patients with diabetes mellitus. Previous diabetes health education and educational status were significant factors associated with greater improvements in self-care behavior. Integrating this digital education approach into routine diabetes management programs at community health centers may enhance patient engagement and support long-term self-care